BUILDING SOLDIERS' HUMAN RESOURCE CAPABILITIES IN FACING SOCIETY 5.0 - Dudung Abdurachman (SEAN Institute, 2023)
Society 5.0 describes the development of a society that is increasingly integrated with advanced technology, such as artificial intelligence, IoT, and robotics. In this context, the role of soldiers in national defense and security becomes increasingly complex. Therefore, this research aims to understand how to build the human resource capabilities of soldiers so they can face and contribute positively to Society 5.0. This research uses a qualitative approach with descriptive methods. Data was collected through in-depth interviews, observation and document analysis. The research results show that the changing paradigm of threats to state sovereignty in the digital era and sophisticated information technology demands rapid adaptation in TNI military training. Non-traditional threats, such as cyber attacks from states and non-state groups, require increased digital literacy, special training in the field of cybersecurity, strong analytical and intelligence capabilities, development of sophisticated defense equipment operating capabilities, soft skills, and strengthening discipline and ethics. . Developing the human resource capacity of TNI soldiers in these aspects is key in maintaining state sovereignty in an increasingly complex era and continuously developing technology. With soldiers who are well trained and committed to the values of integrity and humanity, the TNI is ready to face various challenges that may arise in the future in maintaining the country's security and sovereignty.